STRATEGI DIGITAL MARKETING WISATA KULINER UMKM MELLUI MEDIA SOSIAL DI BERASTAGI TANAH KARO - Tarigan, Nirwaty (Jurnal Akademi Pariwisata Medan, 2025)
Culinary tourism in the tourist area has an important role, where its existence is an inseparable unit of the destination. Therefore, the development of the two tourism companies support each other and have close links. This is seen in the Berastagi tourist destination in Tanah Karo Regency, North Sumatra, where in addition to having beautiful natural scenery and mountains, cool air is also supported by the availability of a variety of traditional Karo culinary processed from raw materials that are processed from raw materials sourced from the natural wealth of the land of Karo itself, making unique, some Asian and Italy foods produced with the taste of Karo which are currently served by many MSMEs (UMKM) in Berastagi Tanah Karo which are expected by sellers or owners of tourist attractions as well as MSMEs (UMKM) culinary tourism, Being one of the culinary tourist attractions and at the same time the introduction of Karo's typical food to tourists who come to visit. This study intends to assess the effect of digital marketing on MSMEs (UMKM) culinary tourism in this case digital marketing through the use of social media as a means of promotion and sales. In addition, this study also examined the application of digital marketing strategies in culinary tourism areas, especially in Berastagi Tanah Karo, North Sumatra. This study uses descriptive qualitative methods, with data collected through interviews, observations, and documentation. Research findings revealed that various successful digital marketing strategy methods in promoting efficient online products or marketing succeeded in achieving targets, one of which was digital marketing through social media that had a positive impact on sales and benefits of MSMEs (UMKM) Culinary Tourism.